Big Blue’s next big act: smarter technology for a smarter planet - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Everything seems to be going digital – our television sets, phones, the ways in which we communicate with each other, perform transactions or apply for permits – all in the name of pristine pictures, crystal clear sounds, paperless administration and fast, unencumbered access to data – all important features of the good life, for sure. But are we necessarily better off? We could be, given that "digitalisation" allows us to see and do things differently; to be more intelligent than we have ever been before, says IT giant IBM. And it is this belief that underscores the company's worldwide "Smarter Planet" initiative, which champions the use of digital technologies in delivering the public good: from preventing crime to curbing energy wastage.